RISKY BEHAVIOR WHEN DRIVING LUXURY CARS: THE PERSPECTIVE OF CAR TRADER - Hendro Prabowo; Mahargyantari Purwani Dewi; M. Ihsan Sulthoni; Henny Regina Salve (Jurnal Transportasi, 2022)
Abstract High-risk behavior, speeding, and breaking traffic on the road by wealthy people while driving their luxury cars are a common phenomenon on roads that often occur in Indonesia and in other countries. This study aims to explore the meaning of driving a luxury car for luxury car dealers who have experience driving several types of luxury cars. The phenomenological method was used in this study, which was conducted through online interviews with several used luxury car dealers. Some of the observed features include the type of luxury car, speed, safety, and security while driving. This study shows that, indirectly, driving a luxury car can be a risky behavior on the road. Keywords: luxury car; phenomenon on roads; speeding; risky behavior on the road. Abstrak Perilaku berisiko tinggi, ngebut, dan melanggar lalu lintas di jalan oleh orang-orang kaya saat mengendarai mobil mewah mereka merupakan fenomena umum di jalan yang sering terjadi di Indonesia dan di negara-negara lain. Studi ini bertujuan untuk menggali makna mengendarai mobil mewah bagi pedagang mobil mewah yang telah memiliki pengalaman mengendarai beberapa jenis mobil mewah. Metode fenomenologi digunakan pada studi ini, yang dilakukan melalui wawancara daring dengan beberapa pedagang mobil mewah bekas. Beberapa fitur yang diamati meliputi jenis mobil mewah, kecepatan, keselamatan, dan keamanan selama berkendara. Studi ini menunjukkan bahwa, secara tidak langsung, mengendarai mobil mewah bisa menjadi perilaku berisiko di jalan. Kata-kata kunci: mobil mewah; fenomena di jalan; ngebut; perilaku berisiko di jalan.